RETRACTED: A Semi-Hexagonal Array (1×2) Antenna Using Half Mode Substrate Integrated Waveguide for Short Range Communication Devices - Munir, M. E.; Qurashie, S. S. (Engineering, Technology & Applied Science Research, 2018)
This article has been retracted at the request of the Editor-in-Chief due to extended similarites with an unpublished paper, written by other authors, that was submitted (but not yet published) to several other journals and was probably leaked during the review process. The authors of the unpublished paper contacted the Editor-In-Chief with the above claim after the publication of this issue and ETASR has contacted several of the journals mentioned and the investigation resulted in the confirmation of the report. The authors of this paper failed to provide any reasoning regarding the case.